Congenital Melanocytic Nevus: An Unusual Presentation: Life Sciences -Pathology - Wajpeyi, Dr. Ketki; Hiwale, Dr. Kishor; Reddy, Dr. Anil (International Journal of Life Science and Pharma Research, 2023)
The overgrowth of melanocytes produces congenital melanocytic nevus. They are commonly present since birth, and the common terms used to describe them are called 'bathing trunk,' 'coat-sleeve,' or 'stocking naevi,' and they are usually found over thighs and back. The giant congenital nevus of size larger than twenty centimeters is highly pigmented and usually hairy. It is more commonly found in females compared to males. It is well recognized that the lesion's displeasing nature might have psychological and social ramifications, negatively affecting the patient's self-esteem, particularly females. Although congenital melanocytic nevus is mostly clinically diagnosed, the histological investigation is required to confirm the diagnosis and rule out malignant changes. The likelihood of transforming the giant nevus to malignant melanoma accounts for approximately five percent; fifty percent of melanomas develop before age two, and eighty percent develop before age seven. The risk of transformation to malignant melanoma is early in giant melanocytic nevus cases and adolescence in small and medium-sized nevi cases. Other complications like transformation to neurocutaneous melanosis consisting of the spread of melanoma to the central nervous system and leptomeninges are also dreadful. Hence, early removal is recommended. Here, we have reported a rare case of a six-year-old patient with a medium-sized nevus on their face with hairy tufts in between. On biopsy, the diagnosis was made as a junctional nevus. After which, the patient was managed with subsequent lesion excision and split skin grafting with an uneventful postoperative period. Our case report aims to report a rare case of congenital melanocytic nevus and to determine the importance of timely diagnosis and intervention. Keywords: , , , ,